2018
DOI: 10.1021/acs.chemrev.7b00667
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Hydroaminomethylation Reaction to Synthesize Amines from Alkenes

Abstract: In the context of atom economy and low environmental impact, synthesis of amines by an efficient catalytic process is of great importance to produce these building blocks for fine chemical industry. The one-pot hydroaminomethylation of alkenes is a tandem reaction which involves three successive steps under CO/H pressure to perform the catalyzed hydroformylation of the alkene into the corresponding aldehyde followed by its condensation with a N-H function and the catalyzed hydrogenation of the imine/enamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
120
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 206 publications
0
120
0
1
Order By: Relevance
“…[3] Traditional methods to effect net hydroaminomethylation involve the two-step sequence of alkene hydroformylation followed by reductive amination (Scheme 1, A). [4] More recently,s everal metal-catalyzed direct hydroaminoalkylation reactions of alkenes have been reported that employ simple alkylamines as the starting materials (Scheme 1, B). [5] These approaches,d ominated by early transition-metal catalysts,have shown some restrictions, in part as aconsequence of the thermodynamically challenging CÀHa ctivation step a to secondary amines and of the traditional incompatibility of early transition metals with oxygen functional groups (with only few notable exceptions [5a,b] ).…”
mentioning
confidence: 99%
“…[3] Traditional methods to effect net hydroaminomethylation involve the two-step sequence of alkene hydroformylation followed by reductive amination (Scheme 1, A). [4] More recently,s everal metal-catalyzed direct hydroaminoalkylation reactions of alkenes have been reported that employ simple alkylamines as the starting materials (Scheme 1, B). [5] These approaches,d ominated by early transition-metal catalysts,have shown some restrictions, in part as aconsequence of the thermodynamically challenging CÀHa ctivation step a to secondary amines and of the traditional incompatibility of early transition metals with oxygen functional groups (with only few notable exceptions [5a,b] ).…”
mentioning
confidence: 99%
“…[7] It has stood and out from a number of synthetic strategies and become an important tool for the highly efficient synthesis of complicated cyclic compounds, especially polycyclic compounds with molecular complexity and structural diversity. [7] It has stood and out from a number of synthetic strategies and become an important tool for the highly efficient synthesis of complicated cyclic compounds, especially polycyclic compounds with molecular complexity and structural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Owing to the various transformation of the aldehyde group,h ydroformylation-initiated tandem reactions towards more complex molecules have been achieved, including hydroaminomethylation, [12] hydroformylation/Fischer indole synthesis, [13] hydroformylation/Wittig reaction, [14] and other tandem processes. [11] Owing to the various transformation of the aldehyde group,h ydroformylation-initiated tandem reactions towards more complex molecules have been achieved, including hydroaminomethylation, [12] hydroformylation/Fischer indole synthesis, [13] hydroformylation/Wittig reaction, [14] and other tandem processes.…”
mentioning
confidence: 99%
“…Rhodium-catalyzed hydroformylation of alkenes represents ah ighly efficient route for the preparation of aldehydes. [11] Owing to the various transformation of the aldehyde group,h ydroformylation-initiated tandem reactions towards more complex molecules have been achieved, including hydroaminomethylation, [12] hydroformylation/Fischer indole synthesis, [13] hydroformylation/Wittig reaction, [14] and other tandem processes. [15] By contrast, asymmetric hydroformyla-tion-triggered cascade reactions have been rarely reported, although intensive research efforts and much progress have been made in asymmetric hydroformylation during the past decades.…”
mentioning
confidence: 99%